INTEGRATING SMARTPHONES IN ENGLISH CLASS AT ELEMENTARY SCHOOL LEVEL: A STUDY ON INDONESIAN ELEMENTARY SCHOOL TEACHER’S PERCEPTION - Resti Purnamasari; Metty Agustine Primary; Yuyus Saputra; Rahmat Rahmat (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
Due to the COVID-19 outbreak, it requires that the learning process, including teaching English at the elementary school level, is carried out with an online learning system. Implementing an online learning system is closely related to the use of technology. Smartphone is one of the technology tools that are widely used in facilitating the online learning process. Hence, the study in this article was to see the perception of an elementary school teacher in integrating smartphones during the English teaching process. Based on the research, the researchers used a case study as a research design, semi-structured interviews, and online observations in collecting the data. Then, the data were analyzed by using thematic analysis, which was also elaborated with the TPACK framework from the theory of Mishra and Koehler in 2006. The study reveals two responses related to the teacher’s perception of using smartphones, namely negative and positive responses. In the negative response, three perceptions generated were (1) ineffective delivery of subject materials, (2) the issue in managing students, and (3) internet access problems. In addition, the positive responses include (1) smartphones as an adequate teaching medium, (2) an affordable platform for smartphones to teach, and (3) YouTube channels as a fun way to learn for young learners. In conclusion, using smartphones in teaching English to students at the elementary school level certainly raised the negative and positive reactions from the teacher during the teaching process. Thus, teaching English to young learners required the teacher’s role to teach technological, pedagogical, and content knowledge adequately.